Strand 2: Vigorous Engagement: Distance Learners, Learner Support, and Libraries - Cowan, Barbara; Parker, Lyn (Proceedings of the International Conference on Networked Learning, 1998)
Distance learners are a growing market for departments of all types in UK universities. Libraries must be able to adapt and fully participate in the move to a library where electronic resources play a leading role. Riggs (1997) summarises by stating: "The current and emerging technology offers an extremely positive environment for improving library services in distance education endeavours. Exciting and rewarding times are ahead for librarians who engage themselves vigorously in distance education". With the introduction of networked collaborative learning through the use of computer mediated communication technology, University Libraries need to determine the most effective ways of providing course readings to students on on-line courses as well as access to information sources, databases. A small survey was undertaken at the University of Sheffield to review the requirements for the on-line courses offered at the Dearne Valley College. Core reading materials can be made available in either traditional formats or electronic. The latter involves applying for copyright permission, scanning the documents and providing user friendly access. A comparison was completed to determine the overall costs of providing materials electronically, via existing short loan collections or in study packs. The move to reliance on electronic resources is a boon to distance learners. With appropriate technology at either work or home they can cap into many of the same resources as their on campus counterparts. A second survey undertaken at the University of Sheffield examined what current support is offered in both old and new universities for distance learners with questions specifically asking about library orientation, WWW pages for distance learners, and what developments librarians in the field expect will come about. This future vision is both exciting and overwhelming. Staffing issues, technological issues, financial issues are highlighted: developing and maintaining electronic support mechanisms is time and labour intensive.